Isolasi dan Karakterisasi Protease Serupa Tripsin (PST) dari Lactobacillus plantarum FNCC 0270 - TRISMILAH TRISMILAH; WAHONO SUMARYONO; AMARILA MALIK; MOHAMAD SADIKIN (JURNAL ILMU KEFARMASIAN INDONESIA, 2014)
Trypsin is an enzyme which is important for research as well as for the pharmaceutical industry, medicine and health, which is especially developed as a raw material for digestive enzymes. This study aimed to characterize PST from Lactobacillus plantarum FNCC 0270 that have not been studied as a producer of trypsin. Fermentation for producing PST by L . plantarum FNCC 0270 was performed in the LKB fermentor with working volume of 3.5 liters, at temperature of 37 oC, pH value of 8, agitation rate of 77 rpm and aeration of 0.5 vvm. The media composition were 3.64% baker’s yeast, 1.21% glucose, 0.13% skim milk. The fementation resulted in enzyme activities of 0.00129 U/mL and protein content of 0.49 mg/mL. Purification of the PST conducted by ultrafiltration Hollow Fiber Catridge 5 kD, presipitated with ammonium sulfate saturated (30-70%), 30 kD membrane polyesthersulfone, ion exchange column chromatography Q-XL and HiTrap affinity column chromatography. All of system increased purity of the crude PST. SDS-PAGE of PST indicated the molecular weights of 47.35; 38.42;21.40 and 12.96 kD. The PST was stable at pH value of 8 and temperature range of 25-35 oC. It is proved that the same half-life was 693.2 minutes. Km and Vmax values of the PST were 0.231 mM and 0.001 U/mL, respectively using N-α-benzoyl-DL-arginine-p-nitroanilide as the substrate. PST was inhibited by EDTA, Ca2+, Zn2+, Mg2+, Mn2+ and specific substrates. Based on the result of characterization of PST from L. plantarum FNCC 0270 can be concluded that the trypsin–like protease (PST) was trypsin.